Purwarupa Perangkat Monitoring Ketinggian Air Tandon Menggunakan TinkerCAD - I Kadek Widiarthawan; I Komang Ari Mogi (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2023)
Along with population growth and urban development, the demand for clean water is increasing. Water reservoirs are an effective solution to this problem, by storing large amounts of water in specially designed tanks. Water reservoirs are one of the important components in the household water supply system. This study aims to make it easier for users to monitor the condition of the water in the reservoir. The tools used are Arduino uno R3, green LED, yellow LED, red LED, ultrasonic distance sensor, DC motor, piezo, push button, and h-bridge motor driver. This system is designed using the prototype method, so that users can easily see real-time water levels via mobile devices.